DISPOSSESSION, ROOTING, COALITIONS AND POLITICAL SUBJECTIVATION ABOUT THE RURAL PAMPEAN PEOPLE AND BANQUINEROS FROM CHACO, ARGENTINA - Rotman, Joaquín (2022)
This paper presents and analyzes socio-communitarian rural processes in the Provinces of Buenos Aires and Chaco, Argentina, documented from 1991 and 2015 –respectively– through a collaborative ethnographys approach and using sociolinguistic methodologies. In order to build a theoretical framework, these disciplines are put in relationship to other areas of knowledge i.e., philosophy, social psychology and sociology. In doing so, it is possible to uncover and interpret actions that otherwise remain invisible, such as singular processes of subjectivation, the creation of coalitions and the struggle against the obliteration of life.